The Fate of Nonoperative Management in Patients with Lytic Spondylolisthesis - Sinha, Siddharth; George, K. Joshi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background There is a lack of consensus within the current literature about the role of nonoperative management in lytic spondylolisthesis. Our objective was to assess the fate that nonoperative management plays in patients diagnosed with lytic spondylolisthesis.Methods Data were collected between May 2015 and February 2020 from 41 patients who were initially referred specifically for instrumented lumbar fixation but were instead planned for nonoperative management as they opted to avoid surgery. Magnetic resonance imaging (MRI) scans were used to determine spondylolisthesis grade, type of deformity, and radiologic features. Patient notes were reviewed to establish management plans. Furthermore, patients were also contacted via telephone to assess their symptoms and disease progression.Results Twenty-six of the 41 patients had lytic spondylolisthesis (63.4%). Of these patients, the male-to-female ratio was 10:16. The median age was 60 (range: 22–76) years. A total of 12 patients were managed nonoperatively for 5 years or longer, with 2 patients showing progression from grade I to II.Conclusion Nonoperative management of lytic spondylolisthesis is a reasonable option in a selected cohort of patients. The longer in duration patients are managed conservatively, the less likely they are to require a surgical intervention. Even severe radiologic foraminal stenosis without radicular pain does not seem to push patients toward surgery. Management decisions must be made on an individual basis. These data can give some reassurance to patients who wish to consider nonoperative management and help guide clinicians.
Keywords: spondylolisthesis; Meyerding classification; Oswestry disability index; nonoperative management